Desenvolvimento de métodos analíticos envolvendo entalpimetria no infravermelho - Tischer, Bruna (2017)
Quality control of food and medicines is largely done using methods recommended in official compendia, including titration and gravimetry, which involve several negative aspects and are at odds with the principles of green analytical chemistry. Enthalpy methods are based on the enthalpy determination of chemical reactions. In the entalpimétrica analysis the quantitative determination of a reagent or catalyst is made through the enthalpy variation of a chemical reaction, that can be measured directly or indirectly. The main approaches for the entalpimetric analysis are thermometric titration, direct injection enthalpymetry (DIE) and flow entalpimetry. However, despite the availability of commercial instruments for this purpose today, these techniques have been replaced and almost disappeared from the literature, probably due to the high cost of microcalorimetry devices and the limitation of the low frequency of analysis, leading to the choice of Other analytical methods. Currently, there is a need for the development of analytical methods that provide quick results, low cost, low reagent consumption and waste disposal, and minimal sample preparation and manipulation. In this study, infrared thermography was, for the first time, combined with enthalpymetry for the determination of different analytes (eg, iron, calcium, sodium, chlorides and acidity) in foods. In this way, the so-called Thermal Infrared Enthalpyimetry (TIE) was established using neutralization, complexation, precipitation and oxidation reactions, in which the temperature variation generated in the reactions for the construction of calibration curves was verified. The TIE was performed on microplates using a multichannel pipette for the addition of the reagents and an infrared camera for monitoring the temperature generated inside the wells after the addition of the reagents. The results of the proposed method were compared with those obtained through conventional (volumetric) techniques recommended in official compendia. In this way, TIE was optimized and validated for the determination of total, fixed and volatile acidity of vinegars, and was also applied in the simultaneous determination of sodium chloride and total acidity of pickle brine. The obtained results showed good agreement with conventional techniques, performing the analyzes in a fast, efficient and with potential to be applied as routine analysis, due to the simplicity, speed and high frequency of analysis. Thus, it has been demonstrated that TIE can be considered an important tool for the determination of several analytes in foods. Also in this work, it was also done the evaluation of the TIE using different cameras (with refrigerated detector or not), in order to verify and compare the performance of infrared cameras for application to TIE. It was verified that a refrigerated camera presents better results, however equipment without refrigerated detector, of lower resolution and of low cost presented excellent and promising results.